Macro and micro-nutrient contents of 18 medicinal plants used traditionally to alleviate diabetes in Nuevo León, Northeast of México - Maiti, Ratikanta; González Rodríguez, Humberto; Kumari, Aruna; Chandra Sarkar, Narayan (Pakistan Botanical Society, Department of Botany, University of Karachi, 2016)
Although several medicinal plants has been documented to alleviate diabetes in Nuevo Leon, Northeast of Mexico, no systematic study has been undertaken to determine the efficacy of these plant species. The present study was undertaken to determine micronutrients (Cu, Fe and Zn) and macro-nutrients (K, Mg and P), C, N and C/N and to select plants with high macro and micronutrient contents for high efficacy in 18 medicinal plants collected from botanical gardens of Forest Science Faculty, UANL, Mexico used in Nuevo Leon in Northeast of Mexico, at the experimental station of Facultad de Ciencias Forestales, Universidad Autonoma de Nuevo Leon. Following standard protocols, carbon and nitrogen were determined using a CHN analyzer (Perkin Elmer, model 2400). Mineral contents were using the wet digestion technique (Cherney, 2000). The present study indicated the presence of large variation in the contents of several macro and micronutrients among these 18 species of medicinal plants utilized traditionally to control diabetes and other diseases in Nuevo Leon, Mexico. Among these species containing high nitrogen content (%) are Moringa oleifera (6.25), Melia azadirachta (5.85), Marrubium vulgare (4.56) and Phoradendron villosum (4.9). The C/N values ranged from 8 to 30. The species having high C/N were Agave macroculmis (30), Arbutus xalapensis (26) and Rhus virens (22). The species Melia azadirachta, Marrubium vulgare, Buddleja cordata, Tecoma stans, Hedeoma palmeri, Phoradendron villosum, Opuntia ficus-indica, Arbutus xalapensis exhibited large variations in the contents of macro and micronutrients which, could be considered to be used effectively for the control of diabetes. Few species viz. Marrubium vulgare, Buddleja cordata, Tecoma stans, Hedeoma palmeri, Phoradendron villosum, Opuntia ficus-indica and Arbutus xalapensis on the basis of high nutrient content with respect to C, N, C/N, Cu, Fe, Zn, K, P and Mg are selected and recommended to control diabetes.